Evaluasi Program Pengembangan Ekonomi Lokal di Yogyakarta ( Study Kasus Pengembangan Desa Wisata Kebonagung Kabupaten Bantul) - Sunan Al adiyat; Nunik Retno; Priyatno Harsasto (Journal of Politic and Government Studies, 2014)
The process of local economic development contained in Bantulimplemented based participatory approach that emphasizes on the analysis ofsectoral , spatial , and marketing and focus on three (3 ) main areas , namelytourism, agriculture and small industries . Post-earthquake economic recoveryprogram integrated LED stated in the Strategic Plan 2008-2010 Bantul . Butactually before the year 2008 there has been some economic recovery programsundertaken by the government , both central and local levels that are one- offs .Referring to the Law No. 26 Year 2007 on Spatial Planning , GovernmentRegulation No. 26 Year 2008 on National Spatial Plan , and Local RegulationsYogyakarta Special Region No. 2 of 2010 on Spatial Planning Special Province ofYogyakarta , the concept and utilization of national spatial strategy and theprovince need to be translated into Spatial Planning Bantul designated as Zonedesignation artificial tourism in the District are in : Tourism Village KebunKebunSupreme Court in the Village , as well as No. 03 of 2004 on Regional TourismDevelopment Master Plan Bantul , also Bantul Regency Decree No.359 wasdeveloped as a tourist village in 2006 and refers to the PEL Sector Policy withCommunity Based Tourism Tourism is developing community -based tourismhave proven themselves resilient consolidate after the earthquake ( Travel villages) , as well as develop a network between a tourist village that lays on RuralTourism Development Policy of local Economic development perspective ,emphasizing the development of rural tourism is an alternative to the economicdevelopment of the people by making tourism as the prime mover ( prime mover )local economy .With reference to the above legislation it is expected that development ofrural tourism Kebonagung collapsed due to lack of government's handling of thevillage and also worse off as a result of an earthquake , it can be developed into avillage that can potentially evolve so beneficial to the welfare of society .This study aims to : 1) determine the local economic developmentprograms in post- quake economic recovery in Bantul district from 2007 through2012 , and 2 ) determine the condition of village development Kebonagung afterthe rise and growing as a tourist village agriculture and culture . While theresearch method used is descriptive qualitative interview guide using the speakers.The results showed that the efforts of the Local Economic Development inPost-Earthquake Recovery Economic Conditions in Bantul during this three (3)major steps , namely : a) careful planning based on accurate data and a singledatabase , which is the basis of all program developed b ) Conduct efforts so thatpoor families reduced the burden of his life , through various assistance that aimsto relieve , reduce , freeing expenses ( costs ) to be incurred families ,and ; 3 )Perform empowerment efforts . The data in question , not just about the amount ,but also with regard to the condition and position of the poor families . This datais projected to show the profile of the poor , including the problems faced .Kebonagung village developments show the rise and increasingly manifest as thedevelopment of the agricultural and cultural tourism village . It can be seen fromthe indicators : a) Quality b) Quantity c) Cost -effectiveness d) Need forSupervision , and e ) Impact nterpersonal.Keywords : Evaluation of Local Economic Development Program, RecoveryEconomic Conditions, Kabupaten Bantul